Centro de Apoio Pedagógico : avaliação dos serviços CAP-MA para educação de pessoas com deficiência visual - Pereira, Josefa Lídia Costa (2011)
This study aims to analyze the impact of services developed by the Center for Educational Support Services for People with Visual Impairment of Maranhão (CAP-MA) in the period 2001 to 2008, based on documentary surveys, observations of services provided for the visually impaired and the general community and in conversations among students, responsible students, and professionals (teachers, technicians of the CAP). The CAP-MA is a federal initiative in partnership with the State of Maranhão and aims to offer a quality educational services to students with visual impairments. The study included 28 teachers from the CAP, ten students with visual impairments, five technicians, responsible for seven blind students and 30 course participants from the community. Were used to collect data three instruments: observation script, documents with information on professionals and students and interview guide. Data collection followed the ethical and methodological referrals needed. For the analysis of data treatment was used qualitative content analysis through the categories captured in different sources. The results showed that both teachers, students, parents, coaches and community in general value the services provided by the Support Center. The teachers feel satisfied with the dynamics of services developed and recognize that the CAP has grown with every passing year. Admitted that it still needs constant deployments because the demands are manifested differently each year. Technicians in turn see the actions of the CAP progress are acquired with commitment of all involved in the process. Working with the heads of students and the proposal to list them on the labor market has been very important nowadays. The family showed feel satisfied with the actions for their children and their families. Students appreciate the new shares of the CAP over the other contest some services due to length of service for those who are placed in regular education. Considering all that has been treated in the results can be inferred that the work of the CAP in general, has brought good results for the population of visually impaired people from across the state. Progress was made over the years, not only the quality of care for students with visual impairments, as well as professionals and the wider community. Partnerships and dissemination has facilitated the recognition of the importance of these services. The State Government is fulfilling its responsibilities as a partner in the federal government, signed since the implementation of the CAP in 2001, the State of Maranhão. Finally, it is important to value the suggestions of professionals, students, family and community at large about the progress of the Center's services to detect, through the.